Synergy of Teacher Profesionalism Development of The Quality of Education - Sunhaji, Sunhaji (International Conference of Moslem Society, 2016)
Teachers are the key in improving the quality of education. They are in a very strategic position for education reformation oriented in quality achievement. The role of teachers is even more strategic in schooling context. Teachers play a major role in the development of education, particularly formal education in schools. Teachers also determine the success of students, especially in learning process. Teachers play the main role in the learning process. The learning process is a process with a course of conduct between teachers and students who are in a reciprocal relationship that takes place in an educational situation in order to achieve certain goals. Any efforts made to improve the quality of education would be meaningless without professional teachers. Therefore, any efforts to reorganize and improve the quality of education must involve teacher empowerment. Professionalism characterized by autonomy, adequate expertise, teachers’ high commitment of their tasks and their passion to improve their skills continuously are the indicators of the teacher’s professionalism. Teacher professional development to improve the professionalism standard related to skills; includes mastery of teaching materials and learning methodologies as well as professional attitude regarding motivation and commitment of teachers in performing their duties, needs to be improved to create synergy towards quality of education.